Integration of FMEA Analysis with Environmental Sustainability Aspects in the Defense Industry a Proactive Approach to Prevent System Risks and Ecological Impacts - Saefullah, Endang; Sudiarso, Aries; Muhammad, Ade (PT FORMOSA CENDEKIA GLOBAL, 2025)
The defense industry plays a strategic role in national security, yet environmental impacts are often overlooked. This study develops an integrated Failure Mode and Effects Analysis (FMEA) framework that incorporates environmental sustainability indicators into critical processes such as ammunition assembly, combat vehicle painting, and explosives storage. A descriptive quantitative approach is applied using FMEA by assessing severity, occurrence, and detection, while also considering hazardous waste, emissions, energy use, and contamination risks. The results show that the failure mode with the highest Risk Priority Number (RPN) is process failure due to human error or non-standard procedures (RPN = 252). Other significant risks include hazardous waste (RPN = 200) and excessive energy/resource use (RPN = 175). These findings emphasize the need for operator training, integrated waste management, and regular energy audits. The study concludes that sustainability-integrated FMEA provides a comprehensive framework aligning operational reliability with ecological responsibility in the Indonesian defense industry.